Treatment of Class II malocclusion with mandibular skeletal anchorage - ÇAKIR, EZGİ; ÇAKIR, EZGİ; Malkoc, Siddik; KIRTAY, MUSTAFA (My University, 2017)
Introduction: The aim of this case report was to present the dentofacial changes obtained with bone anchorage in a Class II patient with moderate to severe crowding. Methods: A boy, aged 14.5 years, with a dolichofacial type, convex profile, and skeletal and dental Class II relationships was examined. After evaluation, functional treatment with bone anchorage and 4 first premolar extractions was decided as the treatment approach. Miniplates were placed on the buccal shelves of the mandibular third molars. The hook of the anchor was revealed from the first molar level. After surgery, the 4 first premolars were extracted to retract the protrusive mandibular incisors. The maxillary and mandibular first molars were banded, and a lip bumper was inserted to apply elastics and to help distalize the maxillary first molars. Orthodontic forces of 300 to 500 g were applied immediately after placement, originating from the miniscrews to the hooks of the appliance to advance the mandible. Results: After 20 months of treatment, the patient had a dental and skeletal Class I relationship, the mandible was advanced, the maxilla was restrained, and overjet was decreased. Conclusions: The combination of a bone anchor, Class II elastics, and an inner bow is a promising alternative to functional treatment, along with extractions, in Class II patients.